The Effect of Dining Atmospherics to Perceived Value, Customer Satisfaction, and Behavioral Intention With Double Decker Restaurant in Solo Baru as Research Object - Rizky Ayu Khoiriyana; Wisnu Untoro (Universitas Sebelas Maret, 2017)
The purpose this study is to examine the impact of Dining Atmospherics, Perceived Value, Customer Satisfaction, and Behavioral Intentions in Restaurant Double Decker at Solo Baru, Indonesia. We distribute questionnaires to 150 consumers of Restaurant Double Decker Solo Baru who visited more than three times. Using Structural Equation Model (SEM) assisted by AMOS application program, the results showed that Behavioral Intention have a significant positive influence on the dependent variable that is Atmospherics, and the dependent variable that is Atmospherics also have a significant positive effect on the mediating variable, Customer Satisfaction, and Perceived Value, then the Customer Satisfaction has a significant positive influence on independent variables of Behavioral Intention.